Pengaruh Jumlah Bahan Dalam Tangki Penyuling Metode Uap dan Air Terhadap Rendemen Serta Mutu Minyak Sereh Wangi (Cymbopogon nardus L. Rendle) - Muhammad Haikal Hirzi; Yurnalis; Inawaty Sidabalok (Jurnal Research Ilmu Pertanian, 2022)
This study aims to determine the effect of the amount of material in the distiller's tank on the yield and quality of citronella oil. The design used in this study was a completely randomized design (CRD) with 5 treatment levels and 3 replications. The results showed that the amount of material in the distiller's tank showed a very significant effect on yield, specific gravity, refractive index value, acid number and ester number, but had no significant effect on oil solubility in alcohol. The highest yield and the best quality of citronella oil were obtained from treatment A (amount of material in the distiller tank 40 kg) with yield (1.30 %), specific gravity (0.8955), Refractive Index (1.4565), acid number (2 ,17), ester number (52.57), solubility in alcohol 80% (1:1) and pale yellow color. Citronella oil produced from all treatments met the quality requirements set by SNI, except for the refractive index